Legal Protection for Criminal Acts Against Disabled Perpetrators - Natasya , Ezika Viki; Reyvan, Achmad Reyvan Fatony; Pramesti , Mei Windi; Ramadani, Layla Maha Putri; Azzahra , Excella Bunga (Universitas Negeri Surabaya, 2025)
The increasing global recognition of disability rights highlights a critical gap in the legal protection of offenders with disabilities. This issue is especially pressing as traditional criminal justice systems often fail to fully address the specific vulnerabilities and needs of individuals with disabilities who come into conflict with the law. These systems frequently lack the necessary accommodations, which may result in continued discrimination and hinder the rehabilitative goals of justice. This study employs normative legal research methods to conduct a comprehensive analysis of relevant laws, regulations, and judicial decisions concerning disabled offenders. The primary aim is to identify deficiencies in the existing legal framework and propose substantive reforms to ensure a more just and equitable application of criminal law. Preliminary findings reveal that while general provisions for vulnerable groups exist, specific and comprehensive protections for disabled offenders remain inadequate. This deficiency often leads to potential miscarriages of justice and obstacles to meaningful rehabilitation. According to the research underscores the urgent need for criminal justice systems to adopt a more inclusive and human rights-based approach in their treatment of individuals with disabilities.